Analisis Ketersediaan Tempat Tidur untuk Pasien Covid-19 pada Rumah Sakit di Daerah Kota Bandung Berbasis Web Siranap - Alfadli M S; Wafi Fahruzzaman; Andaru Danurdara W; Ade Dwi Fatwa; Zahran Hanif F; Muhammad Davio Athallah; Satriyatama Tristan Suhardjono; Yuyun Hidayat; Firman Rezaldi; Fernanda Desmak Pertiwi; Aris Ma’ruf; Retna Yulrosly Ningtias (Universitas Mathla'ul Anwar Banten, 2021)
REPORT OF OBSERVATION OF BED AVAILABILITY FOR COVID-19 PATIENTS AT HOSPITAL IN BANDUNG CITY REGION BASED ON SIRANAP WEB. This observation aims to analyze the level of accuracy and the real time nature of the data on the SIRANAP web conducted by hospitals in the city of Bandung. We did this observation for 16 days by taking screenshots 3 times every day with a random screenshot schedule. This observed update time is then rounded to the nearest 30 minutes to obtain a data resolution. From these observations, it is suspected that the data from seven hospitals in Bandung on SIRANAP website is inaccurate. Of the seven hospitals in the city of Bandung, only one hospital is categorized as real-time, which are Hasan Sadikin General Hospital, the other six hospitals are categorized as not real-time. Based on the standard deviation of SIRANAP data, seven hospitals in Bandung City have different update times. Therefore, it can also be concluded that the data on SIRANAP has not been able to help the people of Bandung City optimally.